SOFIA FEEDBACK Survey: The Pillars of Creation in [C ii] and Molecular Lines - Ramsey L. Karim; Marc W. Pound; Alexander G. G. M. Tielens; Maitraiyee Tiwari; Lars Bonne; Mark G. Wolfire; Nicola Schneider; Ümit Kavak; Lee G. Mundy; Robert Simon; Rolf Güsten; Jürgen Stutzki; et al. (The Astronomical Journal, 2023)
We investigate the physical structure and conditions of photodissociation regions (PDRs) and molecular gas within the Pillars of Creation in the Eagle Nebula using SOFIA FEEDBACK observations of the [C ii ] 158 μ m line. These observations are velocity resolved to 0.5 km s ^−1 and are analyzed alongside a collection of complimentary data with similar spatial and spectral resolution: the [O i ] 63 μ m line, also observed with SOFIA, and rotational lines of CO, HCN, HCO ^+ , CS, and N _2 H ^+ . Using the superb spectral resolution of SOFIA, APEX, CARMA, and BIMA, we reveal the relationships between the warm PDR and cool molecular gas layers in context of the Pillars’ kinematic structure. We assemble a geometric picture of the Pillars and their surroundings informed by illumination patterns and kinematic relationships and derive physical conditions in the PDRs associated with the Pillars. We estimate an average molecular gas density ${n}_{{{\rm{H}}}_{2}}\sim 1.3\,× \,{10}^{5}$ cm ^−3 and an average atomic gas density n _H ∼ 1.8 × 10 ^4 cm ^−3 and infer that the ionized, atomic, and molecular phases are in pressure equilibrium if the atomic gas is magnetically supported. We find pillar masses of 103, 78, 103, and 18 M _⊙ for P1a, P1b, P2, and P3, respectively, and evaporation times of ∼1–2 Myr. The dense clumps at the tops of the pillars are currently supported by the magnetic field. Our analysis suggests that ambipolar diffusion is rapid and these clumps are likely to collapse within their photoevaporation timescales.